Exploratory Temporal and Evolutionary Insights into the Filoviridae Family Through Multiprotein Phylogeny - Thiago S. Messias; Kaique C. P. Silva; Narciso A. Vieira; Gislaine A. Querino; Elaine C. Marcos; Mateus J. de C. Stefani; Ana P. R. Battochio; Thaís M. Oliveira; Ivan S. Vieira; Aline S. Ibanes; Taylor E. T. Olivo; Edson C. de Melo; et al. (Microorganisms, 2025)
Filoviruses are among the most lethal viral human pathogens known, with significant relevance to public health, yet their evolutionary history remains poorly resolved. This study applied a multiprotein molecular phylogenetic approach to investigate the evolutionary and temporal dynamics of the family Filoviridae. Amino acid sequences from the proteome and seven individual proteins (NP, VP35, VP40, GP, VP30, VP24, L) were analyzed using MEGA 12, with RelTime inference anchored on uniform calibrations, and integration of epidemiological data (cases, fatalities, case fatality). The phylogenetic reconstructions revealed robust topologies for most proteins, though selective pressures on GP, VP30 and VP40 generated more variable patterns. Temporal inferences supported the classification of filoviruses into three groups: an ancestral lineage (>1 MYA, fish- and reptile-associated), an intermediate lineage (BCE–1 MYA, bat-associated), and a contemporary lineage (CE, ebolaviruses and marburgviruses). VP30 and VP40 showed consistent associations with epidemiological outcomes in Orthoebolavirus zairense, suggesting their interplay may underlie enhanced dispersal and virulence. Contrariwise, Orthoebolavirus restonense emerged as a natural counterpoint for comparison with other potential human pathogenic filoviruses. Taken together, these findings highlight that filoviral evolution is intrinsically linked not only to viral biology but also to the ecology and history of their hosts.